Improving the high temperature oxidation resistance of TiAl alloy by SiOC coating - Yun-Yang Li; Hao-Jie Yan; Lian-Kui Wu; Fa-He Cao (Journal of Materials Research and Technology, 2023)
To improve the high temperature oxidation resistance of TiAl alloy, silicon oxycarbide (SiOC) coating was fabricated by dip-coating using polydimethylsiloxane (PDMS) as the precursor. The oxidation behavior of the coating was evaluated at 850 °C. The morphology and chemical structure of the SiOC coating were characterized by scanning electron microscopy (SEM) equipped with an energy dispersive spectroscopy (EDS), Fourier Transform infrared spectroscopy (FT-IR), X-ray photo electron spectroscopy (XPS), and X-ray diffraction (XRD). Results showed that the SiOC coating exhibited good oxidation resistance. During the thermal exposure, the selective oxidation of Al at the SiOC/TiAl alloy interface resulted in the generation of protective Al2O3, which suppressed the inward diffusion of oxygen and outward diffusion of the alloy matrix elements. However, the cracks on the surface of SiOC coating were observed, which would provide channels for the oxygen and form thermally grown oxide layer (mainly consisting of TiO2 and Al2O3) above the Al2O3 layer.